2011
DOI: 10.1115/1.4004280
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Fabric Impact With High Speed Imaging and Nickel-Chromium Wires Validation

Abstract: Ballistic tests were performed on single-yarn, single-layer and ten-layer targets of Kevlar® KM2 (600 and 850 denier), Dyneema® SK-65 and PBO® (500 denier). The objective was to develop data for validation of numerical models so, multiple diagnostic techniques were used: (1) ultra-high speed photography, (2) high-speed video and (3) nickel-chromium wire technique. These techniques allowed thorough validation of the numerical models through five different paths. The first validation set was at the yarn level, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 32 publications
4
61
0
2
Order By: Relevance
“…Chocron et al [30] have reported data from yarn shooting experiments involving 0.3 caliber, FSP projectiles impacting Kevlar ® S5705, Dyneema ® SK65 and Zylon ® PBO yarns. For a range of incremental impact velocities, it was determined whether or not yarns fail immediately by evaluating frames from high speed video.…”
Section: Experiments On Ballistically Measured Yarn Modulus and Strenmentioning
confidence: 99%
“…Chocron et al [30] have reported data from yarn shooting experiments involving 0.3 caliber, FSP projectiles impacting Kevlar ® S5705, Dyneema ® SK65 and Zylon ® PBO yarns. For a range of incremental impact velocities, it was determined whether or not yarns fail immediately by evaluating frames from high speed video.…”
Section: Experiments On Ballistically Measured Yarn Modulus and Strenmentioning
confidence: 99%
“…In order to circumvent this high variability measurement, a more appropriate method has been pursued wherein one tracks the difference in longitudinal wave travel times from projectile-yarn contact site to the detection of the longitudinal wave from the clamping load cells for drastically different yarn lengths L 1 and L 2 ; L 1 and L 2 are measured as 10.3 cm and 73.2 cm, respectively. Such a measurement is described in Equation (10) and is demonstrated in Figure 3. As previously stated, possessing accurate L 1 and L 2 is achieved using a laser bore site, allowing for Equation (10) to provide an accurate estimate of the wave speed of the yarn material.…”
Section: Longitudinal Wavementioning
confidence: 99%
“…Such a measurement is described in Equation (10) and is demonstrated in Figure 3. As previously stated, possessing accurate L 1 and L 2 is achieved using a laser bore site, allowing for Equation (10) to provide an accurate estimate of the wave speed of the yarn material. As an aside, it is important to note that the longitudinal stress wave must also travel through the yarn clamping fixtures, but accounting for this travel time is unnecessary if identical clamping fixtures are used on both ends of the yarn; the longitudinal wave travel time through the clamps is identical in both fixtures and is inherently subtracted out using the aforementioned time difference method.…”
Section: Longitudinal Wavementioning
confidence: 99%
See 2 more Smart Citations